Maternal mortality : report of meeting held at Friends' House. Euston Road on November 15, 1932 (London : Maternal Mortality Committee)
1932-11 1932 1930s 36 pages The question of ante-natal care is one which is occupying all our attention, but midwives feel that sometimes public money is wasted in the ante-natal clinics unless they are places where they can get obstetrical consultants, because the need for the continuity of the care of the mother is not recognised. I think the Report also stresses very strongly that the attendant upon the mother, the doctor who does the overhaul, should be the one called in in an emergency, and the midwife who is responsible for the birth should be with the mother throughout pregnancy. If we could have, as I believe some enlightened Authorities are providing, ante-natal clinics, places where midwives and doctors can bring their patients for examination using all the technical appliances necessary to-day, and where they can obtain obstetrical experts' help and advice, we should then be able to see much more co-operation between midwives, local practitioners, and the Local Authorities. Finally, I want to appeal for what a great American woman has called "pooled intelligence." The three Reports finally dispose of the theory that midwives are entirely responsible for the prevention of Maternal Mortality. We are all responsible, every one of us, and while great minds have been working on the problem now for years we do not think enough has been made of the common sense and the knowledge of the working midwife and the working mother whom she serves. I should like to see in every area a local Round Table Conference set up, Round Table Conferences are the fashion to-day, and I think if we could see all who are concerned represented at local round table conferences to thrash out together what schemes are possible for the locality, how much money is available, and what is the best way to deal with it, I think we should go a very long way towards solving the problem of Maternal Mortality. I read in a Report the other day of an Indian Training School for Midwives, somebody asked one of them : "If such and such happened, what would you do ?" And the Indian midwife answered : "I should trust in God and use my common sense." Now there is common sense if we can only get it, and if we can get the combination of the common sense of the midwives and the working mothers and of the great minds we shall solve this problem. I have much pleasure in seconding the resolution. Miss ELEANOR RATHBONE, M.P. : Lady Iveagh and ladies and gentlemen, there are some meetings which seem to exist for the education of the audience, and there are other meetings of which the main value seems to be the education of the speakers. And I am not sure that this most impressive gathering does not belong to the latter kind of meeting, because though we all know the very deep interest that the Minister of Health takes in his subject, you who comprise most of the audience are engaged in (17) 292/824/1/45